Produção de enzimas extracelulares por Ceratocystis spp. - Firmino, Ana Carolina [UNESP]; Furtado, Edson Luiz [UNESP] (FapUNIFESP (SciELO), 2014)
The genus Ceratocystis includes several species distributed over several parts of the world. In Brazil there are reports of the existence of three species: C. cacaofunesta, C. paradoxa and C. fimbriata, the latter being related to disease in crops of economic importance. This study aimed to determine, in specific culture media, the production of the extracellular enzymes amylase, lipase, cellulase, protease, laccase, lignin peroxidase and pectiliase (pectatelyase) for isolates of Ceratocystis spp. A total of 41 isolates were used: 3 from mango (Mangifera indica), 19 from eucalyptus (Eucalyptus spp.), 15 from cocoa (Theobroma cacao), 2 from Teak (Tectona grandis) and 2 from atemoya (Annona sp.). The colonies were incubated in the dark at 25°C, except for the medium for pectinase detection which was incubated under alternating photoperiod. Experimental design was completely randomized with 4 replicates. The specific media allowed the detection of the production of amylase, laccase and protease for almost all tested isolates of Ceratocystis sp. Production of cellulase, lipase and pectatelyase was not observed. Production of the enzyme lignin peroxidase was detected in small amounts and in only a few isolates of the fungus. This enzymatic profile obtained from the fungus population may assist in future studies related to its characterization.
Extracellular enzyme production by Ceratocystis spp.
Keywords: Characterization; Enzymes; Fungi